The Innovation of Information and Communication Technology in Contextual Teaching and Learning Models Based PAI Learning - Luqman Hakim; Anfasa Naufal Reza Irsali; Tsamarah Nabilatul Watsiqoh (Universitas Muhammadiyah Malang, 2023)
The integration of technology in the era of the Fourth Industrial Revolution has become essential in various aspects of human life, including education. This study aims to explore the implementation of technology-based Islamic Religious Education learning at MAN 1 Lamongan in response to the challenges and demands of the digital era. The method used in this study involves analyzing teaching materials, interviewing Quran and Hadith teachers, and students from Madrasah Aliyah Negeri 1 Lamongan, as well as observing classroom learning. The implementation of ICT-based learning in the Contextual Learning and Teaching model consists of two stages: the design stage and the implementation stage conducted by the teachers. The implementation stage is further divided into three phases: (a) opening, which involves delivering and teaching Islamic Education knowledge materials; (b) implementation, where students engage in group projects to connect the material with real-world events and their own experiences; and (c) closing, which includes reflection and evaluation of the learning process related to the studied material. Throughout the learning process, students are given the freedom and support to utilize technology, including laptops/smartphones and software applications such as Google Chrome, Microsoft Office, YouTube, WhatsApp, and free Wi-Fi access, to facilitate their learning. The study results indicate that using ICT-based learning media for Al-qur’an Hadith in this model has successfully increased students' interest in learning, enhanced their critical thinking skills, and fostered their creative competence in understanding and processing information and knowledge collaboratively.